Implementasi Permensos Nomor 1 Tahun 2018 Tentang Program Keluarga Harapan Dalam Penanggulangan Kemiskinan di Desa Ngrji Kecamatan Purwodadi Kabupaten Grobogan: IMPLEMENTATION OF PERMENSOS NUMBER 1 OF 2018 CONCERNING FAMILY HOPE IN POVERTY REDUCTION IN NGRAJI VILLAGE, PURWODADI DISTRICT, GROBOGAN REGENCY - Fabyanti, Enjel Gansar; Haryanto, Aris Tri; Suhita, Damayanti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2023)
Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program in Ngraji Village, Purwodadi District, Grobogan Regency aims at poverty reduction. This thesis leads to how to implement the Family Hope Program in Ngraji Village. The subjects in this study were companions of the family hope program, heads of ngraji villages, family beneficiaries (KPM) of the family hope program, and heads of family hope program groups. This research was analyzed using the theory of implementation developed by George C. Edward III which refers to indicators of Communication, Resources, Disposition, and Bureaucratic Structure. This type of research is Descriptive Qualitative. Data collection techniques used are interviews, observations, documentaries and informant determination techniques carried out by Snowball Sampling. The results showed that the communication variables carried out by the companion of the family hope program had been carried out smoothly. Group meetings are held regularly, but in consistency the KUBE (Joint Business Group) program has not been implemented in Ngraji village. Variable resources, assistance staff owned by PKH have carried out their duties well, PKH facilities have been established, namely beneficiary families get automated teller machine cards and can be picked up at E-waroeng. The authority of Ngraji Village in implementing the family hope program has an important role in the running of the program. Disposition variables, the commitment of family program assistants has provided effective and efficient services, the provision of incentives to PKH assistants is given through the Regional Budget (APBD) of Grobogan Regency. The variables of bureaucratic structure, meknism are in accordance with the regulation of the Minister of Social Affairs Number 1 of 2018 and the fragmentation or spread of responsibility carried out by ngraji villages is less firm in stopping family hope program assistance Keywords : Communication, Resources, Disposition, Bureaucratic Structure